A fractional-order model of COVID-19 and Malaria co-infection - Iwa, Livinus Loko; Omame, Andrew; Inyama, Simeon Chioma (Fırat Evirgen, 2024)
This paper explores the co-infection dynamics of coronavirus disease 2019 (COVID-19) and Malaria using Caputo-type fractional derivative to further understand the disease interactions and implement effective control strategies. We demonstrate the positivity and boundedness of the solution through Laplace transform techniques and establish the existence and uniqueness of the solution, showcasing model stability using fractional-order stability theory. Simulation experiments across varying fractional orders and disease classes offer insights into the co-infection dynamics. This is a new model and the findings underscore the potential impact of control measures on mitigating co-infection under endemic conditions. We conclude that infection with malaria does not guarantee immunity to COVID-19 and infection with COVID-19 as well does not guarantee immunity to malaria.
Keywords: Biological Mathematics; Biyolojik Matematik; Applied Mathematics (Other); Uygulamalı Matematik (Diğer)